Identifying The Critical Factors Influencing The Adoption Of Information Systems Among International Hotels In Klang Valley - Ghorbankhani, Ali (2009)
This study identifies the critical factors that influencing the adoption of Business Information Systems among international hotels in Klang Valley. The results of review literatures stated that the factors are significantly affecting the adoption decision of Business Information Systems (BIS) could be devided into three major categories which are organization related factors, operational related factors and strategic related factors.